Model Integratif Dalam Menelusuri Motivasi dan Preferensi Perjalanan Pada Wisatawan Lansia di Sumatera Barat - Eka Mariyanti; Murry Harmawan Saputra; Puti Embun Sari; Siska Lusia Putri; Widia Ananda (CV. ITTC INDONESIA, 2026)
The increasing number of senior tourists has intensified the need for tourism destinations that prioritize comfort, healthcare, safety, and high-quality travel experiences. Senior tourists represent an important market segment to be studied because they generally possess greater leisure time, stronger financial stability, and higher tourism expenditure tendencies compared to other age groups. West Sumatra has significant potential to become a senior-friendly tourism destination through its rich cultural, religious, culinary, and natural tourism attractions; however, the development of the senior-friendly tourism concept remains suboptimal. This study aims to analyze the relationships among self-determined motivation, tour preferences, memorable experience, emotions, perceived benefits, and life satisfaction of senior tourists visiting West Sumatra. This research employed a quantitative approach using the SEM-PLS method. The study sample consisted of 320 pre-senior and senior tourists who had previously visited tourism destinations in West Sumatra, determined using the Raosoft sample size calculator. The findings reveal that self-determined motivation and tour preferences significantly influence memorable experience. Furthermore, perceived benefits exert the strongest influence on senior tourists’ life satisfaction. The study also confirms that perceived benefits mediate the relationship between memorable experience and emotions toward senior tourists’ life satisfaction. Padang and Bukittinggi emerged as the most preferred destinations due to their cultural, religious, culinary, and natural tourism attractions that align with the characteristics and preferences of senior tourists. This study concludes that memorable tourism experiences and perceived benefits play a crucial role in enhancing senior tourists’ life satisfaction. The implications of this research highlight the importance of developing a senior-friendly tourism concept through improvements in accessibility, destination cleanliness, safety, healthcare facilities, rest areas, and slower-paced travel packages to sustainably support the quality of life of senior tourists.